The Founders’ 400 and Chicago Perinatal Origins of Disease study protocol: Following a prospective, longitudinal cohort from early pregnancy through two years of postnatal life - Stephanie A. Fisher; Tonia N. Branche; Mary J. Akel; Jessica Dwyer; Gabriella Smith; Aaron Hamvas; Lynn M. Yee; Patrick C. Seed; Leena B. Mithal (PLoS ONE, 2025)
Introduction The primary aim of the Chicago Perinatal Origins of Disease (CPOD) study is to characterize social, environmental, and biological exposures from early pregnancy through two years of postnatal life among a diverse cohort of mother-fetus/child dyads in the Chicago metropolitan community and to examine associations with pregnancy and early childhood health outcomes. This study is committed to ensuring the inclusion of participants historically underrepresented in perinatal research and most impacted by perinatal health inequities. CPOD is designed to align with key stakeholder and community input. Methods Approximately 400 pregnant people 8–28 weeks gestation and their neonates will be recruited into a longitudinal, prospective observational study enriched for participants who self-identify as Black and/or Latinx. Pregnant participants are followed at three time points antenatally and during their delivery hospitalization; mother-child dyads are followed at five time points in the first two years of life. Semi-structured interviews, patient-reported quantitative surveys, electronic health record abstraction, biological specimens, and environmental sampling from participant homes comprise data collection methods. Biospecimens (including placental biopsies) from mothers, infants, and other household members are collected, processed, and stored in a biorepository. Translational approaches, including a variety of biospecimen analyses (e.g., epigenetics, metabolomics, placental histopathology, microbiome analyses), will be employed to evaluate psychosocial and environmental exposures associated with biologic changes, and how dysregulation of one’s underlying biology during pregnancy and early childhood are associated with adverse health outcomes. Discussion CPOD is a unique, prospective, observational study that includes a large, ethnically diverse cohort; rich, multifactorial phenotypic characterization of maternal health and pregnancy outcomes, neonatal health, and early childhood neurobehavior; and development of a biorepository of social, environmental, and clinical data and biospecimens from early pregnancy to two years of postnatal life. Using translational science approaches, data from this cohort will provide clinical and mechanistic insights into how environmental and psychosocial exposures, both during pregnancy and transgenerationally, influence changes in the underlying biology of maternal-child dyads, and how these changes are associated with the risk of adverse health outcomes that contribute to future disease.